Murder Mystery Solved with the Help of Forensic Investigation - Mukesh Sharma; Deepak Sharma (Brazilian Journal of Forensic Sciences, Medical Law and Bioethics, 2020)
Crime scene reconstruction is the process of determining or eliminating the events that occurred at the crime scene by analysis of physical evidences. In one case, a lady left the house receiving a call on her cell phone. Since she did not return home till late evening, the husband and her children made search but could not trace out. Subsequently, a missing report was lodged in the local police station. At night, on the same day, the dead body of the missing lady was found lying in a bathroom of a Hotel along with a male dead body. The investigative and forensic team visited the undisturbed crime spot. Scrutiny of forensic evidence, crime scene dynamics, victimology and autopsy study could establish the case to be murder and suicide. At crime scene, on the basis of our observations the two cases were registered under murder and suicide IPC sections. The male murdered the lady in the bathroom and committed suicide near the dead body of the lady. This involved scientific crime scene investigation, interpretation of patterned evidence at the scene, laboratory testing of the physical evidence, systematic study of related case information, and the logical formulation of a theory gives the proper directions to the Investigating officer (IO). In this article, we have reported an interesting case for forensic aspect. The IO, was in this impression, it might murder. Our team, reveals the truth and case was solved at scene of crime.